A STUDY ON AWARENESS AND SATISFACTION OF WOMEN TOWARDS GOLD JEWELLERY WITH SPECIAL REFERENCE TO TIRUNELVELI - Nivetha, A.; Jebaraj, S. Prince (ShodhKosh: Journal of Visual and Performing Arts, 2024)
From ancient times to the present day, gold has served as a powerful symbol of wealth, power, and prestige, adorning the crowns of kings and the sacred relics of religious institutions. But beyond its material value, gold has also come to represent deeper concepts such as purity, enlightenment, and the divine. It gives the security against any financial crisis, because of its easy liquidity, and is also used by women for adorning themselves. For Indians, jewellery holds immense significance both in a cultural and religious sense. They also form an integral part of various ceremonies and festivities, such as weddings, cultural festivals, and religious rituals. Similarly, jewellery play a vital role in Indian culture and traditions. Besides, it is often passed down through generations, representing family heritage and traditions. This paper analyses consumer level of awareness and satisfaction towards buying behaviour of gold jewellery. The data required for the study collected form women through well-structured interview schedule and analysed the data with the help of statistical tools such as garrett ranking, weighted average score, etc. so as to draw a meaningful conclusions.